PENGGUNAAN NOMINA DALAM SURAT KABAR HARIAN TRIBUN - Haris Abdul Wasik; Nusarini Nusarini (Universitas Sarjanawiyata Tamansiswa, 2017)
The purpose of this research was to describe (1) the form of the noun used in the Tribun newspaper, and (2) describe the behavior of the noun syntax in the Tribun newspaper. Type of this research is qualitative descriptive research. The research data in the form of sentences in which there are nouns or noun in the Tribun newspaper in September 2015. The source of data was obtained from the Tribune newspaper. Data collection techniques in this study using advanced engineering methods and see which consists of several techniques which refer to the techniques involved skilled and technical notes. The data analysis technique used in this research is the method agih with techniques vanished, insertion technique, and many reading techniques. The presentation of the results of data analysis used informal methods. The results showed that (1) the form of the noun used in the Tribun newspapers are the basic nouns and nouns derived. Derivative nouns are found include nouns formed with affix, reduplication and compounding. Affixes forming derivative noun are afiks per -, afiks peng-, afiks an-, afiks peng- -an, afiks per–an, afiks keâ€”an. Reduplication results include intact repeated words, repeated words accompanied affix, the word repeated part, and the word re-copy the sound. Results of compounding include basic compound nouns, compound nouns affixed, terraced compound nouns and plural nouns equivalent. (2) Syntactic behavior of nouns in the daily newspaper Tribune found covering the noun as a function of the subject, predicate function, the function of the object, and complementary functions.